POSITIVE ADAPTATION IN LATINO FAMILIES OF CHILDREN WITH DEVELOPMENTAL DISABILITIES: AN INITIAL TEST OF POSITIVE ADAPTATION THEORY - Aldana, S. I.; Singer, G. H.S.; Maul, C. A.; Magaña, A.; Esparza, S. I. (Critical Disability Discourses, 2010)
Historically, research on disability and family dynamics drew from Psychology and Medicine. Consequently, eugenics models, grief theory, and other largely decontextualized frameworks of stress and coping were used to explain families of children with disabilities. This is a report of an initial test of a set of ideas the Singer research team has combined in order to explore the cognitive and problem-solving approaches of families of children with disabilities. Our purpose is to propose a contextualized theory for explaining how cultural diversity has an impact on positive adaptation to a child’s disability. This theory addresses the following: 1) attachment; 2) internal and external cultural resistance to stigmas about disability; and 3) perceived informal (family/friends) and formal (professionals) sources of support for positive views about disability and parenting. Sampling Latino families demonstrated how cultural contexts demonstrate a different flavour from majority culture interpretations of these cognitive terms of our proposed theory. Transcripts of the interviews were coded using grounded theory analysis, specifically, the constant comparative method. We discuss the goodness of fit for themes emerging from the coding process with the proposed theory terms. Results confirm attachment, social supports, and cultural resistance as terms for future development of this proposed theory. Keywords: Disability and parenting, positive adaptation, Latinos and disability, culture and disability